“Cool” dan “Hot” Brain Executive Functioning dan Perfomansi Akademik Siswa - Nani Restati Siregar (Buletin Psikologi, 2018)
The study of literature was to aim of exploring the role of cool and hot executive functions (EF) on academic performance. It was consist of (a) what are they; (b) developmental hot and cool EF; and (c) The dynamic of hot and cool EF toward academic performance. This study of literature explores a distinction (and relationship, too) made within this general domain that has emerged only recently in the theoretical and empirical literature: cool and hot executive function. Cool executive functions were related to cognitive tasks (working memory, cognitive flexibility, inhibition control), and hot executive functions were related to emotion tasks (motivation, effective decision making, behavior). Both of them played an important role in academic performance. The implication of the literature study should be useful for teaching strategy in the classroom. Teachers need to create a good atmosphere, in particular, to stimulate positive emotions for learners